Research progress and development tendency of polymer drilling fluid technology for unconventional gas drilling - He, Yinbo; Jiang, Guancheng; Dong, Tengfei; Wang, Guoshuai; He, Jing; Dou, Huanjun; Du, Mingliang (Frontiers in Energy Research, 2023)
Unconventional gas includes tight sandstone gas, shale gas, coalbed methane, and natural gas hydrate. With huge reserves, unconventional gas has become the most important natural gas resource successor after the end of the “Easy Oil era.” The drilling fluid is an indispensable wellbore working fluid for unconventional gas drilling with multiple functions. The polymer drilling fluid (PDF) is the most common, longest developed, and most diverse drilling fluid type. With advantages of easily controlled rheology, convenient on-site performance maintenance, and specifically low cost and weak environment pollution, the PDF is gradually replacing the oil-based drilling fluid as the first choice for unconventional gas drilling. The invention of the non-disperse low-solid-content PDF in the 1960s shows that PDF technology has entered the stage of scientific development, and until now, its development has generally experienced five stages: beginning, developing, improving, re-developing, and re-improving. Dozens of polymer additives and PDF systems have been invented and applied, which have solved severe drilling problems, greatly improved drilling efficiency, and promoted exploration and development in difficult oil and gas resources. This paper first reviews the research progress of PDF technology according to the timeline by introducing the composition, feature, advantages, and disadvantages of some representative polymer additives and PDF systems, emphatically the function and mechanism of stabilizing wellbores, lubricating drilling tools, and protecting reservoirs of the biomimetic wellbore-strengthening PDF and amphiphobic high-efficiency PDF in unconventional gas drilling. Then, combining future global demands, especially China’s strategic needs of oil and gas exploration and development, the development tendency of PDF technology is critically illustrated by introducing several potential research directions including intelligent PDF, ecological PDF, and PDF for natural gas hydrate and deep layer gas resources.